2020
DOI: 10.1016/j.jccase.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Relative bradycardia as a clinical feature in patients with coronavirus disease 2019 (COVID-19): A report of two cases

Abstract: We treated two patients with COVID-19 pneumonia requiring mechanical ventilation. Case 1 was a 73-year-old Japanese man. Computed tomography (CT) revealed ground-glass opacities in both lungs. He had severe respiratory failure with a partial pressure of oxygen in arterial blood/fraction of inspiratory oxygen ratio (P/F ratio) of 203. Electrocardiogram showed a heart rate (HR) of 56 beats/min, slight ST depression in leads II, III, and aVF, and mild saddle-back type ST elevation in leads V1 and V2. High-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[4][5][6][7][8][9][10] Two papers speak specifically to associations between COVID-19 and relative bradycardia in adults, seen in states of high metabolic demand such as increased body temperature during which tachycardia would be expected. [11][12][13] One study found that one-third of adult patients with severe COVID-19 infection but overall stable vital signs developed sinus bradycardia at some point during the course of their illness. 4 Additionally, there are reports of adult patients infected with COVID-19 who develop bradycardia related to medications such as lopinavir-ritonavir, 14 hydroxychloroquine and other QT-interval-prolonging medications 15 and of course sedating medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] Two papers speak specifically to associations between COVID-19 and relative bradycardia in adults, seen in states of high metabolic demand such as increased body temperature during which tachycardia would be expected. [11][12][13] One study found that one-third of adult patients with severe COVID-19 infection but overall stable vital signs developed sinus bradycardia at some point during the course of their illness. 4 Additionally, there are reports of adult patients infected with COVID-19 who develop bradycardia related to medications such as lopinavir-ritonavir, 14 hydroxychloroquine and other QT-interval-prolonging medications 15 and of course sedating medications.…”
Section: Discussionmentioning
confidence: 99%
“… 4–10 Two papers speak specifically to associations between COVID-19 and relative bradycardia in adults, seen in states of high metabolic demand such as increased body temperature during which tachycardia would be expected. 11–13 One study found that one-third of adult patients with severe COVID-19 infection but overall stable vital signs developed sinus bradycardia at some point during the course of their illness. 4 …”
Section: Discussionmentioning
confidence: 99%
“…3 Bradycardia in COVID-19 appears to be an important cardiac manifestation that has a multifactorial etiology and is increasingly becoming a characteristic clinical finding in patients with COVID-19. It has been described in isolated case reports, 4,5 a limited case series 6 defined as relative bradycardia with heart rate (HR) < 90 beats per minute (BPM) 7 and through a survey sent among cardiac electrophysiologists. 3 In Southern California, there have been a multitude of patients with COVID-19 with variable presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Relative bradycardia is considered the most reliable and sensitive parameter when applied to cases where the body temperature is >38.9°C (102°F). Faget sign was named in honor of Jean Charles Faget (1818-1884) and initially reported in cases of yellow fever (42)(43)(44). Relative bradycardia has been described in a variety of infectious and noninfectious conditions, including a host of viral illness.…”
Section: Cardiovascularmentioning
confidence: 99%
“…Relative bradycardia has been described in a variety of infectious and noninfectious conditions, including a host of viral illness. Although the mechanism is unknown, it has been hypothesized that it may be caused by a direct pathogenic effect on the myocardium or nodal tissue, inflammatory cytokines increasing the vagal tone and decreasing the heart rate variability or systemic autonomic dysregulation, or a possible link between angiotensin-converting enzyme 2 (ACE2), the receptor for COVID-19, and its expression on cardiac cells regulating autonomic heart rate control (44)(45)(46).…”
Section: Cardiovascularmentioning
confidence: 99%